Computational Study of Preliminary Steps of Artelasticin Synthesis Reaction Mechanism from Catechin: Solvent Effect Analysis on Thermodynamics and Kinetics of Reaction - Eduardus
Indonesia is the seventh largest tea exporter country in the world. However, in the last 5 years, tea export from Indonesia declined because it lacks of competitiveness to the other tea product from other countries. One potential of tea that can be developed is the utilization of catechin compound because it has 30% contents from dry weight. The computational study of preliminary step (elimination step) of artelasticin compound (P388 antitumor compound with LC50 = 3.0 ?g/mL) from catechin has been conducted. This reaction involves polar compound and solvent along with ionic species, then the effect of water solvent is studied. The result shows that the solvent does not significantly change compounds' structure, with changes in bond length and angle mostly below 1%, with the máximum changes of 4.7%. Thermodynamically, the reaction will spontaneously happen until the formation of cation with rearrangement, but to get the eliminated compound, it needs a higher temperature because the reaction is endothermic. The solvent effect changes the thermodynamic of protonation reaction from exothermic to endothermic, and the tendency of protonation changes from the ether’s oxygen to hydroxy’s oxygen. From the kinetic aspect, the activation energy is very low, so the tunneling effect is suspected to be dominant because of the reaction involving proton with a very small mass. The effect of water solvent changes both thermodynamic and kinetic aspect of the reaction.